2011
DOI: 10.1149/1.3572292
|View full text |Cite
|
Sign up to set email alerts
|

Physics-Based Hot-Carrier Degradation Modeling

Abstract: We present and verify a physics-based model of hot-carrier degradation (HCD). This model is based on a thorough solution of the Boltzmann transport equation. Such a solution can be achieved using either a stochastic solver based on the Monte Carlo approach or a deterministic counterpart that is based on representation of the carrier energy distribution function as a series of spherical harmonics. We discuss and check two implementations of our model based on these methods. The model is verified vs. the HCD exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
2

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(16 citation statements)
references
References 91 publications
0
14
0
2
Order By: Relevance
“…This concept has resulted in the so-called energy driven paradigm proposed in [9] and [10]. However, in [11] and [12], we have shown that the maximum of the interface state density N it coincides neither with the electric field nor with the average carrier energy. Instead, another quantity that is called the carrier acceleration integral (AI) was identified to properly describe HCD [13], [14].…”
mentioning
confidence: 87%
“…This concept has resulted in the so-called energy driven paradigm proposed in [9] and [10]. However, in [11] and [12], we have shown that the maximum of the interface state density N it coincides neither with the electric field nor with the average carrier energy. Instead, another quantity that is called the carrier acceleration integral (AI) was identified to properly describe HCD [13], [14].…”
mentioning
confidence: 87%
“…Under stress conditions with high drain voltages carriers can be accelerated up to energies exceeding the bonding energy of the Si-H bond which is E a = 2.6 − 2.9 eV [46][47][48] and therefore they are able to trigger bond rupture in a single collision. This scenario is called "single-carrier mechanism" of bond dissociation and was dominant in high-voltage devices and/or old technology nodes [49][50][51]. Under lower drain voltages these highly energetical carriers have low concentrations and therefore the single-carrier mechanism has a negligibly low rate.…”
Section: Defect Generationmentioning
confidence: 99%
“…Это, однако, сугубо искусственный пример: на практике деградация, вызываемая горячими носителями, является сильно неоднородным явлением и профили N it имеют выраженный пик около точки отсечки транзистора [8,9,22].…”
Section: предварительная оценка масштаба эффектаunclassified